Incidence of Cardiovascular Events in Patients Treated With Immune Checkpoint Inhibitors. Issue 29 (10th October 2022) - Laenens, Dorien; Yu, Yuling; Santens, Béatrice; Jacobs, Johanna; Beuselinck, Benoit; Bechter, Oliver; Wauters, Els; Staessen, Jan; Janssens, Stefan; Van Aelst, Lucas
Abstract : PURPOSE: In rare cases, immune checkpoint inhibitors (ICIs) cause immune-mediated myocarditis. However, true incidence of other major adverse cardiovascular events (MACEs) after ICI treatment remains unknown, mainly because late occurring side effects are rarely reported in prospective clinical trials. The aims of this study were (1) to identify incidence and risk factors of MACE in a real-life ICI-treated cancer cohort and (2) to compare incidence rates with patients with cancer who are not treated with ICIs and population controls. METHODS: In total, 672 patients treated with ICIs were included. The primary end point was MACE, a composite of acute coronary syndrome, heart failure (HF), stroke, and transient ischemic attack. Secondary outcomes were acute coronary syndrome and HF separately. Incidence rates were compared between groups after matching according to age, sex, cardiovascular history, and cancer type. RESULTS: The incidence of MACE was 10.3% during a median follow-up of 13 (interquartile range, 6-22) months. In multivariable analysis, a history of HF (hazard ratio 2.27; 95% CI, 1.03 to 5.04; P = .043) and valvular heart disease (hazard ratio 3.01; 95% CI, 1.05 to 8.66; P = .041) remained significantly associated with MACE. Cumulative incidence rates were significantly higher in the ICI group compared with the cancer cohort not exposed to ICI and the population controls, mainly driven by a higher risk of HF events. CONCLUSION: Cardiovascular events during and after ICI treatment are more common than currently appreciated. Patients at risk are those with a history of cardiovascular disease. Compared with matched cancer and population controls, MACE incidence rates are significantly higher, suggesting a potential harmful effect of ICI treatment besides the underlying risk.